The Pacific Island Health Care Project - Donald Ames Person (Frontiers Media S.A., 2014)
Introduction/BackgroundUS Associated/Affiliated Pacific Islands (USAPI) include 3 Freely Associated States: Marshall Islands, Federated States of Micronesia, Palau and 3 Territories: American Samoa, Guam, and Commonwealth of the Northern Mariana Islands. ObjectiveThe Pacific Island Health Care Project (PIHCP) provides humanitarian medical referral/consultation/care to >500,000 indigenous people of these remote islands. Methods In the mid-1990s, we developed a simple store-and-forward program to link the USAPI with Tripler Army Medical Center (TAMC). This application allowed image attachment to email consultations. ResultsMore than 8000 Pacific Islanders have benefited from the program. 3000 Pacific Islanders prior to telemedicine (1990-1997) and since store-and-forward telemedicine (1997-present), the PIHCP has helped an additional 5000. Records post dynamically and are stored in an archival database. Conclusion The PIHCP is the longest running telemedicine program in the world delivering humanitarian medical care. It has bridged the Developing World of the remote Pacific islands with advanced medical and surgical care available at a major US military teaching hospital.(The opinions expressed here are those of the author and not that of the Army, Department of Defense, or the US Government.)